Prediction of physical activity based on the BASNEF model constructs during preconception period among women referred to Uremia health centers - Roghieh Bayrami; Alireza Didarloo; Afsaneh Asadinejad (Tehran University of Medical Sciences, 2020)
Background & Aim: Physical activity is a health behavior that helps onechr('39')s mental and general health, improves the health of women during preconception period and reduces pregnancy and birth complications. The aim of this study was to predict physical activity based on the BASNEF model constructs during preconception period among women referred to Uremia health centers. Methods & Materials: This cross-sectional study was conducted on 230 women during preconception period, who were selected using the multistage sampling method in 2018. The data collection tool was a researcher-made questionnaire containing sociodemographic information, the BASNEF model constructs, and a short form of the international physical activity questionnaire. Data were analyzed using logistic and linear regression and t-test through the SPSS software version 16. Results: The results showed that 61.3% of women had low levels of physical activity. Knowledge (β=0.2, P<0.003), attitude (β=0.15, P<0.017), and enabling factors (β=0.18, P<0.004) significantly explained their intention to do physical activity. Also, among the predictive variables, knowledge (P<0.001) significantly explained physical activity. Conclusion: Low rate of womenchr('39')s physical activity during preconception period calls for designing an intervention based on BASNEF model in order to influence knowledge, attitude and enabling factors.